2012
DOI: 10.1002/lt.23493
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients with hepatorenal syndrome after living donor liver transplantation

Abstract: Liver transplantation (LT) is the treatment of choice for hepatorenal syndrome (HRS). However, the clinical benefits of living donor liver transplantation (LDLT) are not yet well established. We, therefore, investigated the outcomes of patients with HRS who underwent LDLT and patients with HRS who received transplants from deceased donors. This study focused on 71 patients with HRS out of a total of 726 consecutive adult Korean patients who underwent LT at a single Asian center. We compared 48 patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…We were not able to determine the incidence of hepatorenal syndrome (HRS) prior to transplant, and therefore were not able to test the effect of HRS on the subsequent development of post-transplant CKD. However, recent single center studies have found equivalent renal outcomes in LDLT and DDLT patients with HRS (21, 22). Our analysis adjusted for serum creatinine at the time of transplant, and, although serum creatinine is an imperfect proxy for the magnitude of pre-existing renal dysfunction in patients with liver disease, there is no reason to think that serum creatinine differentially represents renal dysfunction in LDLT versus DDLT candidates, However, before drawing strong inference from our findings, they should be validated by other groups.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to determine the incidence of hepatorenal syndrome (HRS) prior to transplant, and therefore were not able to test the effect of HRS on the subsequent development of post-transplant CKD. However, recent single center studies have found equivalent renal outcomes in LDLT and DDLT patients with HRS (21, 22). Our analysis adjusted for serum creatinine at the time of transplant, and, although serum creatinine is an imperfect proxy for the magnitude of pre-existing renal dysfunction in patients with liver disease, there is no reason to think that serum creatinine differentially represents renal dysfunction in LDLT versus DDLT candidates, However, before drawing strong inference from our findings, they should be validated by other groups.…”
Section: Discussionmentioning
confidence: 99%
“…reported that eight patients out of 32 (25%) died within the first month after DDLT . It was also reported that in‐hospital mortality was significantly higher in HRS recipients than in non‐HRS . In this regard, however, it has not been fully elucidated why the short‐term outcome in HRS patients is worse than in non‐HRS.…”
Section: Discussionmentioning
confidence: 99%
“…23 It was also reported that in-hospital mortality was significantly higher in HRS recipients than in non-HRS. 12 In this regard, however, it has not been fully elucidated why the short-term outcome in HRS patients is worse than in non-HRS. In the present study, there was no difference in the causes of death within 1 year after LDLT between Group-HRS and Group-Non-HRS (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, warnings regarding inferior outcomes of LDLT in high acuity/high MELD candidates also served as deterrents . This was the context surrounding the 3 seminal reports from 3 leading LDLT centers worldwide specifically focused on LDLT for candidates with HRS, as defined by the International Ascites Club (Table ) …”
Section: Ldlt For Patients With Hrsmentioning
confidence: 99%